Psychological Barriers to a Peaceful Resolution: Longitudinal Evidence from the Middle East and Northern Ireland. (3rd August 2018) - Canetti, Daphna; Hirsch-Hoefler, Sivan; Rapaport, Carmit; Lowe, Robert D.; Muldoon, Orla T.
ABSTRACT: Does individual-level exposure to political violence prompt conciliatory attitudes? Does the answer vary by phase of conflict? The study uses longitudinal primary datasets to test the hypothesis that conflict-related experiences impact conciliation. Data were collected from Israeli Jews, Palestinians, and Protestants and Catholics in Northern Ireland. Across  both contexts, and among both parties to each conflict, psychological distress and threat perceptions had a polarizing effect on conciliatory preferences. The study highlights that experiences of political violence are potentially a crucial source of psychological distress, and consequently, a continuing barrier to peace. This has implications in peacemaking, implying that alongside removing the real threat of violence, peacemakers must also work toward the social and political inclusion of those most affected by previous violence.